Curtin University mentor programme: Connecting every beginning student to a mentor - Beltman, Susan; Elliott, J.; Smith, A.; Lynch, E. (The Higher Education Academy & Ashton University, 2013)
Curtin University co-ordinates a campus-wide student mentor program in which every commencing undergraduate student is provided with a senior student from their own course as a mentor. The mentor program has the goal of enhancing student experience as new students are assisted in making a successful transition in to the university. The program effectively manages the risk of new student attrition as mentors assist with campus and information systems orientation, with academic and social components of student life and with connecting new students to support services.